Development of edible gelatin composite films enriched with polyphenol loaded nanoemulsions as chicken meat packaging material. Issue 1 (1st January 2020) - Khan, Muhammad Rehan; Sadiq, Muhammad Bilal; Mehmood, Zaffar
ABSTRACT: In this study, food grade nanoemulsions (NEs) were prepared with polyphenols (curcumin, gallic acid and quercetin); NEs were incorporated into the film forming solution at various concentrations (5%, 10% and 20% v/w of gelatin plus carrageenan). Moisture content and water solubility of film samples decreased with increasing NE concentration. Curcumin NE-loaded gelatin composite films exhibited highest antioxidant activity (27.20 ± 0.02, 45.9 ± 0 and 60.51 ± 0.36%) at 5%, 10% and 20% NE concentrations, respectively. Curcumin NE-loaded composite gelatin films also exhibited antimicrobial activity against both Salmonella typhimurium (6.97 ± 0.03 mm) and Escherichia coli (7.47 ± 0.09 mm). The chemical finger printing of films was evaluated by Fourier-transform infrared spectroscopy. Curcumin NE-loaded films showed excellent results by increasing the shelf-life of fresh broiler meat up to 17 days in comparison to control (10 days), hence can be used as alternative to conventional packaging.